Maternal Access to Health Services by Pregnant Mothers in Bacnotan, La Union, Philippines - Titus, Auta Tanko (Health Notions, 2018)
Understanding variables that influence accessibility and health-seeking patterns of pregnant mothers is necessary for possible intervention of behavioural change. The research was conducted in District 1 of LA Union, City of San Fernando, Philippines to ascertain accessibility and utilization of maternal health services by pregnant mothers in Philippinesâ weak maternal health services delivery. The major purpose of the study was to determine the maternal access/utilization of pregnant mothers in Bacnotan district hospital regarding facilitating/hindering factors in accessing pregnancy related services. Descriptive method of research with the questionnaire was the main data gathering tools employed. Weighted mean were utilized to treat the data. The analysis of the gathered data indicate that the some pregnant mothers do not availed services at their convenient time due to understaffing of the health facility, some could not receive support from their husbands and spouse/relatives, while Some of them encountered barriers along traditional beliefs held by them and their spouse/partners. Based on the findings, Insight into facilitators and barriers to accessing/utilization of health services in this population revealed tools for enhancing engagement in health promotion programs addressing healthy lifestyle and the need for the management to employ more staff, design modality for outreach advocacy to the community members regarding support to the mothers and address other health related issues including barrier along traditional beliefs.